2019
DOI: 10.20524/aog.2019.0426
|View full text |Cite
|
Sign up to set email alerts
|

Association between irritable bowel syndrome and asthma: a meta-analysis and systematic review

Abstract: Background:Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder often seen in outpatient clinics. Diagnosing IBS is often challenging, as it frequently presents with other complicated rheumatological and psychiatric conditions. Asthma has often been associated with gastrointestinal conditions such as gastroesophageal reflux disease and eosinophilic esophagitis. This review and meta-analysis aimed at a better understanding of the association between the conditions.Methods:A comprehensive lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…Furthermore, asthma patients have increased enteric permeability compared to healthy persons, making them more prone to IBS symptoms. 17 In our study, no significant difference in asthma was found between the IBS and non-IBS groups, even though the odds ratio was quite high at 3.1 in patients with a history of asthma. This result was similar to a meta-analysis that reported a pooled IBS odds ratio in adults to be 2 (95%CI 1.5 to 2.8).…”
Section: Discussioncontrasting
confidence: 66%
“…Furthermore, asthma patients have increased enteric permeability compared to healthy persons, making them more prone to IBS symptoms. 17 In our study, no significant difference in asthma was found between the IBS and non-IBS groups, even though the odds ratio was quite high at 3.1 in patients with a history of asthma. This result was similar to a meta-analysis that reported a pooled IBS odds ratio in adults to be 2 (95%CI 1.5 to 2.8).…”
Section: Discussioncontrasting
confidence: 66%
“…Generally, depression and anxiety are highly associated with medical conditions such as hypertension (Ginty et al, 2013). A recent publication on systematic review suggested a strong association between IBS and asthma was probably explained by immune system activation and increased intestinal permeability, a link between hyperresponsiveness in atopy and enteric nervous system (Deshmukh et al, 2019). The exact mechanism was not fully understood on how one condition such as IBS leads to another condition such as asthma, or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Yilmaz et al reported an odds ratio of 2.65 (95% CI, 1.25-5.57), meanwhile, Ozol et al reported an odds ratio of 3.21 (95% CI, 1.53-6.70) in their study [ 5 , 6 ]. A meta-analysis showed a I 2 value of 0% (P=0.8) and an OR of 2.6 (95%CI 1.9-3.5) [ 13 ]. In a study by Kennedy et al, they found that IBS, GERD, and symptomatic bronchial hyper-reactivity occur more frequently together than expected, and these conditions are independently associated with each other [ 14 ].…”
Section: Discussionmentioning
confidence: 99%